Pengaruh Kepemimpinan Transaksional Kepala Ruangan terhadap Pelaksanaan Asuhan Keperawatan Perawat Pelaksana - Mohammad Nisyar Azis; Tri Kurniati; Giri Widakdo (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to determine the effect of head room transactional leadership on the implementation of nursing nurses' nursing care. The design of this study was Quasy Experiment with pre and post test design with control group. The results of the analysis of transactional leadership data have a significant effect on the implementation of nursing care in the intervention group with a p-value of 0,000 <0.05. Whereas in the control group there were differences in the pre and post measurement values of week VI of the Implementation of Nursing Care with a p-value of 0,000 <0.05. Conclusion, in the intervention group it was found that the measurement of the implementation of the first, second, and third post nursing care had a significant increase from 77.55 to 105.45 but not yet reached the optimal value. Keywords: Transactional Leadership, Implementation of Nursing Care